Vinster med björkinblandning i granbestånd i syfte att höja markens pH-värde - Johansson, Maja; Vikberg, Matilda (SLU/Dept. of Forest Ecology and Management, 2012)
The soil acidification and the pH-value of the soil have been discussed for many years. Many observations of the tree species effects on the soil pH have been done. We have discussed the effects on the soil surface pH-value with a birch (Betula spp. L.) admixture in Norway spruce stands (Picea abies L.).We have used data from the Swedish National Forest Inventory. We have also discussed how the wood production and the biodiversity can be increased in mixed stands, in according to the Swedish forestry act Skogsvårdslagen. Our sampling areas are located in Norrland, Sweden.